Medical costs of fourteen occupational illnesses in the United States in 1999 - Leigh, J Paul; Yasmeen, Shagufta; Miller, Ted R (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'This study estimated the annual medical costs associated with 14 occupational illnesses in the United States in 1999. ' ' METHODS ': 'National data sets collected by the National Center for Health Statistics, the Health Care Financing Administration, and the Agency for Healthcare Research and Quality were aggregated and analyzed. The cost assessment began with estimates of national health expenditures. These included categories for hospital care, professional services, nursing homes, and medical products, including drugs, administration, public health activities, research and construction. The total disease burden was assessed from estimates of hospital days and number of outpatient visits. The occupational disease burden was assessed by multiplying the total disease burden by a given percentage of the proportionate attributable risk (PAR) for the disease in question. The occupational burden was then combined with costs for each disease. Adjustments were made for unique inpatient and outpatient costs. ' ' RESULTS ': 'In the preferred model, the 14 diseases generated USD 14.5 billion in medical costs in 1999. Roughly USD 10.7 billion was attributed to men and USD 3.8 billion to women. The diseases generating the most costs were as follows: circulatory diseases in the age group 24-64 years (USD 4.7 billion), cancer (USD 4.3 billion), chronic obstructive pulmonary disease (USD 2.2 billion), and asthma (USD 1.5 billion). A sensitivity analysis generated alternative estimates. An upper age limit of 74 years increased the circulatory disease estimate by USD 3.7 billion. The range of the sensitivity analysis was USD 9.6-19.7 billion. ' ' CONCLUSIONS ': 'This study significantly improves over the methodology of previous literature. Our methods were transparent. Occupational illnesses were a major contributor to the total cost of medical care.
Keywords: economics; job; medical cost; occupational illness; Occupational Safety and Health Administration; OSHA; United States